2015
DOI: 10.3389/fevo.2015.00075
|View full text |Cite
|
Sign up to set email alerts
|

The role of cVA and the Odorant binding protein Lush in social and sexual behavior in Drosophila melanogaster

Abstract: Social living is beneficial because it allows conspecifics to interact in ways that increase their chances of survival and reproduction. A key mechanism underlying these benefits is the ability to recognize conspecifics; thus, allowing the production of coordinated social interactions. Identification of such individuals is often through chemical communication: the individuals' pheromonal profile indicates their sex, species, and even past experiences. However, we know little about how the chemosensory system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 86 publications
3
40
0
Order By: Relevance
“…cVA is a male-specific pheromone produced in the ejaculatory bulb of the male reproductive tract and transferred to females within the ejaculate 20 21 22 23 . cVA reduces male courtship and delays mating when it is either present in the environment 15 or artificially applied to the female cuticle 13 14 24 25 . Two odorant receptor neurons in the antennae 26 27 that express either Or67d 28 or Or65a 29 respond to cVA and both are involved in the cVA-induced male courtship inhibition 15 24 .…”
mentioning
confidence: 99%
“…cVA is a male-specific pheromone produced in the ejaculatory bulb of the male reproductive tract and transferred to females within the ejaculate 20 21 22 23 . cVA reduces male courtship and delays mating when it is either present in the environment 15 or artificially applied to the female cuticle 13 14 24 25 . Two odorant receptor neurons in the antennae 26 27 that express either Or67d 28 or Or65a 29 respond to cVA and both are involved in the cVA-induced male courtship inhibition 15 24 .…”
mentioning
confidence: 99%
“…7-T is one of the compounds that is transferred onto females during copulation and stays on them much longer than most seminally transferred compounds (Yew et al 2009;Everaerts et al 2010). cVA, on the other hand, is now viewed as a regulator of response to other pheromones by increasing or decreasing repulsion that is already there to modulate the intensity of specific social behaviors (Billeter and Levine 2015;Billeter and Wolfner 2018). cVA must be sensed in conjunction with 7-T to influence aggression (Wang et al 2011) and courtship behavior (Laturney and Billeter 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mated females have increased levels of male courtship inhibitory pheromones due to their mechanical transfer during copulation (Scott 1986;Ejima et al 2007). These include the wellcharacterized cVA and 7-T pheromones (Kurtovic et al 2007;Lacaille et al 2007;Billeter et al 2009;Billeter and Levine 2015;Laturney and Billeter 2016). D. simulans females have much higher concentrations of 7-T on their cuticles compared to D. melanogaster females (Jallon and David 1987), and several studies have shown that 7-T recognition is essential for preventing courtship by D. melanogaster males toward heterospecific females (Scott 1986;Lacaille et al 2007;Fan et al 2013).…”
Section: Mir-957 Ko Males Show a Reduced Inhibitory Response To Animamentioning
confidence: 99%
“…MAPLE’s capacity to handle individual flies in combinatorially complex experimental designs ( Figure 3 ), allowed us to demonstrate that dyadic fly social behavior relies on both visual and olfactory cues. Dependence of social behavior on visual ( Mery et al, 2009 ; Simon et al, 2012 ) and olfactory cues ( Schneider et al, 2012 ; Billeter and Levine, 2015 ) is known from experiments observing many flies simultaneously. We further found that individual differences in dyadic social behavior — as well as derived social interaction network topography — remain stable over days ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%